2014
DOI: 10.1007/s40261-014-0213-2
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label Dose Optimization of Methylphenidate Modified Release Long Acting (MPH-LA): A Post Hoc Analysis of Real-Life Titration from a 40-Week Randomized Trial

Abstract: Background and ObjectivesIn the management of attention-deficit hyperactivity disorder (ADHD) in adults it is important to recognize that individual patients respond to a wide range of methylphenidate doses. Studies with methylphenidate modified release long acting (MPH-LA) in children have reported the need for treatment optimization for improved outcomes. We report the results from a post hoc analysis of a 5-week dose optimization phase from a large randomized, placebo-controlled, multicenter 40-week study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…In ten of the studies, participants were adults aged between 18 and 65 years. 15 , 31 33 , 45 , 51 55 , 65 Of the 2,783 participants included in these studies, 1,498 were males. In 33 of the studies, participants were aged between 3 and 17 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In ten of the studies, participants were adults aged between 18 and 65 years. 15 , 31 33 , 45 , 51 55 , 65 Of the 2,783 participants included in these studies, 1,498 were males. In 33 of the studies, participants were aged between 3 and 17 years.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies, 27 did not provide information on the methods or definitions employed in the reporting of side effects. In one of the studies, side effects were reported if experienced by at least 1% of participants, 28 in four studies the cutoff was at least 2% of participants, 26 , 29 , 32 , 49 in one study at least 3% of participants, 24 in seven studies at least 5%, 25 , 30 , 33 , 44 , 54 , 55 , 61 , 65 and in two studies at least 10%. 31 , 66 Two of the studies recorded the most commonly observed side effects only.…”
Section: Resultsmentioning
confidence: 99%
“…In a randomized, placebo-controlled trial (Figure 1), Huss et al53 reported that several doses of MPH-LA (40, 60, and 80 mg) were determined to be optimal for a similar number of ADHD patients (n=152, n=177, and n=160, respectively). Further analysis of the MPH-LA study data showed that this was irrespective of the initial dose administered during Period 1 (Figure 2; previously unpublished data).…”
Section: Dose Optimization In Clinical Trials and Naturalistic Studiesmentioning
confidence: 99%
“…Huss et al designed the only clinical trial (NCT01259492) including both fixed- and flexible-dose phases that directly investigated the benefits of flexible-dose regimens 34,53. This MPH-LA trial encompassed both fixed- and flexible dosing in a single patient cohort (Figure 1).…”
Section: Mph-la Clinical Trial: Design and Analysismentioning
confidence: 99%
See 1 more Smart Citation